If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 + 1 + r + 2r = 2 + r Combine like terms: 4 + 1 = 5 5 + r + 2r = 2 + r Combine like terms: r + 2r = 3r 5 + 3r = 2 + r Solving 5 + 3r = 2 + r Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '-1r' to each side of the equation. 5 + 3r + -1r = 2 + r + -1r Combine like terms: 3r + -1r = 2r 5 + 2r = 2 + r + -1r Combine like terms: r + -1r = 0 5 + 2r = 2 + 0 5 + 2r = 2 Add '-5' to each side of the equation. 5 + -5 + 2r = 2 + -5 Combine like terms: 5 + -5 = 0 0 + 2r = 2 + -5 2r = 2 + -5 Combine like terms: 2 + -5 = -3 2r = -3 Divide each side by '2'. r = -1.5 Simplifying r = -1.5
| x-49+5x=35 | | 3.60+2x=7.20 | | L=2h(l+w) | | 7-5(y+1)=2-5y | | 3+2x=3.60 | | 4x+13-3x+17=-3 | | 0.05x-1.6=0.02x-1.3 | | 91-113=-6(-4y)-13(2y)+y | | 3+x=3.60 | | -3=4(-3)2 | | 2x+7y=-22 | | 7x-79+6x=51 | | 1=8n | | 3x+10=x+7 | | 25=4g-23 | | -12q+8q=-4 | | 19-3x-9xy= | | 5(5y-4)-(7y+4)= | | -49+19=-4x+10x | | A=2h(l+w)forl | | 2b^4-13b^2-45=0 | | a-(3+7b)= | | 1+7x=-11+3x-6+2 | | 0=9x^2-97x+200 | | 3v-3=12 | | M+15=12 | | 3x-23-x=9 | | 9+3x-6x=36 | | 0.30x=430 | | b+1=2b-3 | | -3=2w+3 | | a^2+a-3-3a^2-5= |